Tautinio atgimimo lietuviškos spaudos istorija ir jos kūrėjas: subjektyvioji versija - Kaunas, Domas (Knygotyra, 2005)
This publication includes a letter from a literary worker of the Lithuanian national movement in Lithuania Minor, Martynas Jankus (1858–1946), to a professor of Baltic studies at the University of Göttingen, Eduard Hermann (1869–1950), written in 1929. The letter consists of a reply to a question from the linguist about the state of the Lithuanian press at the end of the nineteenth and the beginning of the twentieth centuries. The author of the letter characterized the publishing of the illegal press in Lithuania Minor and its secret transportation to Lithuania under the rule of Tsarist Russia. He wrote about the most significant literary and publishing workers and the problems of the publishing trade. The letter provides rich biographical data on Martynas Jankus.